2018
DOI: 10.1016/j.devcel.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila Tumor Suppressor Gene Prevents Tonic TNF Signaling through Receptor N-Glycosylation

Abstract: Drosophila tumor suppressor genes have revealed molecular pathways that control tissue growth, but mechanisms that regulate mitogenic signaling are far from understood. Here we report that the Drosophila TSG tumorous imaginal discs (tid), whose phenotypes were previously attributed to mutations in a DnaJ-like chaperone, are in fact driven by the loss of the N-linked glycosylation pathway component ALG3. tid/alg3 imaginal discs display tissue growth and architecture defects that share characteristics of both ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 90 publications
4
38
0
Order By: Relevance
“…It is thought that Grnd binds Egr, prevents its diffusion, and hence controls the autonomy of cell death -it was shown that wing imaginal disc clones overexpressing egr were eliminated via apoptosis, and co-expressing RNAi against Tak1 prevented that autonomous cell death, but co-expressing RNAi against grnd prevented autonomous cell death while also promoting non-autonomous cell death (Andersen et al, 2015). Interestingly, proper identification of a classic Drosophila tumour suppressor gene, lethal(2)tumorous imaginal discs, as ALG3, alpha-1,3-mannosyltransferase (Alg3), has shed light on how Grnd might be regulated -Alg3 mutants fail to glycosylate (and thus inactivate) Grnd, enabling persistent TNF-JNK signalling activation via Egr secreted by the fat body, which promotes JNK-mediated tissue overgrowth via SWH signalling inhibition and Yki activation (de Vreede et al, 2018). Furthermore, Grnd is likely to be involved in both polarity-impairment-induced cell competition and cooperative tumourigenesis -clones with scrib knockdown die, while those with knockdown of both scrib and grnd survive, and the invasiveness of Ras85D V12 /scrib −/− tumours is blocked via grnd knockdown, as is their overexpression of the JNK target, Mmp1 (Andersen et al, 2015).…”
Section: Tnf-jnk Signallingmentioning
confidence: 99%
“…It is thought that Grnd binds Egr, prevents its diffusion, and hence controls the autonomy of cell death -it was shown that wing imaginal disc clones overexpressing egr were eliminated via apoptosis, and co-expressing RNAi against Tak1 prevented that autonomous cell death, but co-expressing RNAi against grnd prevented autonomous cell death while also promoting non-autonomous cell death (Andersen et al, 2015). Interestingly, proper identification of a classic Drosophila tumour suppressor gene, lethal(2)tumorous imaginal discs, as ALG3, alpha-1,3-mannosyltransferase (Alg3), has shed light on how Grnd might be regulated -Alg3 mutants fail to glycosylate (and thus inactivate) Grnd, enabling persistent TNF-JNK signalling activation via Egr secreted by the fat body, which promotes JNK-mediated tissue overgrowth via SWH signalling inhibition and Yki activation (de Vreede et al, 2018). Furthermore, Grnd is likely to be involved in both polarity-impairment-induced cell competition and cooperative tumourigenesis -clones with scrib knockdown die, while those with knockdown of both scrib and grnd survive, and the invasiveness of Ras85D V12 /scrib −/− tumours is blocked via grnd knockdown, as is their overexpression of the JNK target, Mmp1 (Andersen et al, 2015).…”
Section: Tnf-jnk Signallingmentioning
confidence: 99%
“…While membrane-bound Eiger is a juxtacrine signalling molecule, acting only on directly contacting cells, it can also be cleaved from the cell by TNFα converting enzyme 19 and act at a distance, propagating the apoptotic signal further away and resulting in large groups of cells dying 20 . While this process is still not completely understood, it is thought to be important in tissue remodelling 21,22 . Interestingly, in certain cellular contexts such as in the presence of oncogenic Ras, Eiger can have tumour-promoting activity resulting in cellular overgrowth 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Biotin incorporation into proteins of interest was then analyzed by western blot. Western blotting was performed as described previously (71). Primary antibodies are listed in Table 1.…”
Section: Acyl-biotin Exchange (Abe)mentioning
confidence: 99%